2020
DOI: 10.3390/polym12092096
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ultrasonic Treatment on Physicochemical, Structural and Morphological Properties of Sodium Alginate/AgNPs/Apple Polyphenol Films and Its Preservation Effect on Strawberry

Abstract: An antibacterial and anti-oxidation composite film was prepared by a casting method using sodium alginate (SA) and apple polyphenols (APPs) as the base material and glycerol as the plasticizer. Silver nanoparticles (AgNPs) were deposited by ultrasonic-assisted electrospray method. The degree of influence of the addition ratio of SA and AgNPs and different ultrasonic time on the mechanical properties, barrier properties, optical properties, and hydrophilicity of the composite film was explored. The composite fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 77 publications
2
22
0
Order By: Relevance
“…The simple alginate film presented an average value for WVP when compared similar reports [30,83]. The higher value can be explained by the glycerol addition, whic The oxidation process of alginate matrix starts after 200 • C, when multiple exothermic effects, with low intensity, can be observed on DSC curve (inset of Figure 8).…”
Section: Water Vapor Permeability (Wvp)supporting
confidence: 61%
See 2 more Smart Citations
“…The simple alginate film presented an average value for WVP when compared similar reports [30,83]. The higher value can be explained by the glycerol addition, whic The oxidation process of alginate matrix starts after 200 • C, when multiple exothermic effects, with low intensity, can be observed on DSC curve (inset of Figure 8).…”
Section: Water Vapor Permeability (Wvp)supporting
confidence: 61%
“…Therefore, it is important to determine the values for WVP (Table 4). The simple alginate film presented an average value for WVP when compared to similar reports [30,83]. The higher value can be explained by the glycerol addition, which generates hydrogen bonds with alginate and therefore increases the inter-chains distance, allowing moisture to penetrate easier [84].…”
Section: Water Vapor Permeability (Wvp)mentioning
confidence: 74%
See 1 more Smart Citation
“…The obtained values for WVP determination are presented in Table 5 . The WVP value for the alginate control (A) film is average when compared with literature [ 92 , 94 ] due to addition of glycerol, as this will form hydrogen bonds with the base polymer, which further increase the chain–chain distance [ 95 ]. Nevertheless, important decreases in WVP are observed for all samples when compared with alginate control film.…”
Section: Resultsmentioning
confidence: 99%
“…This was probably due to the presence of AgNPs, as they are highly toxic to a wide range of microorganisms [ 13 ]. Other authors have also shown an extension of the shelf life of other food products through the use of films with AgNPs such as: mini kiwi [ 7 ], red grapes [ 45 ], and strawberries [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%